Acute Lung Injury In Pneumonias - V. V Moroz; A. M. Golubev; A. N. Kuzovlev; T. V. Smelaya (Общая реаниматология, 2008)
The review of the literature considers the etiology and pathogenesis of acute lung injury (ALI) in pneumonias. The development of ALI in pneumonias is largely determined by the properties of microorganisms and by the features of the macroor-ganism. The pathogenic properties of microorganisms lead to a damage to the air-blood barrier and to an impairment of the local protective mechanism in the lung. Alveolar damage, a systemic inflammatory reaction, and extracardiac pulmonary edema provoke ALI in pneumonias. The authors show it difficult to make a differential diagnosis and important to detect the early signs of ALI in pneumonias of various genesis. Transpulmonary thermodilution and identification of the markers of alveolar epithelial damage are promising methods. Key words: acute lung injury, pneumonia, sepsis, cytokines, transpul-monary thermodilution.